2003
DOI: 10.1002/ange.200250770
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Cyclic Tetrathiophosphates with Carboxylic Acids as a Means to Generate Dithioesters and Control Radical Polymerization By RAFT

Abstract: Radikalkettenpolymerisationen von Styrol mit (Meth)acrylsäuremethylester können durch eine Kombination aus Davy‐Reagentien oder P4S10 und Benzoesäure kontrolliert werden. In situ gebildete Dithioester (siehe Schema) steuern als Kettenüberträger die Reaktion. Im System P4S10/PhCOOH ist Dithiobenzoesäure ein Schlüsselintermediat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…These include the reaction of benzyl chloride [9,123] or a benzyl sulfone [124] with elemental sulfur in the presence of base, reaction of phenyl Grignard reagent with carbon disulfide, [9] and treatment of benzoic acid with P 4 S 10 or Davey reagent. [121,125] …”
Section: Synthesis Of Raft Agentsmentioning
confidence: 99%
“…These include the reaction of benzyl chloride [9,123] or a benzyl sulfone [124] with elemental sulfur in the presence of base, reaction of phenyl Grignard reagent with carbon disulfide, [9] and treatment of benzoic acid with P 4 S 10 or Davey reagent. [121,125] …”
Section: Synthesis Of Raft Agentsmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] We have recently shown that dithioesters can be obtained in just one step from the reaction of P 4 S 10 (or Davy reagents) with a carboxylic acid in the presence of an alkyl bromide -or radical source -and can be used in situ to control free-radical polymerizations by a RAFT-type mechanism. 54 This report describes (i) the synthesis of multifunctional dithioesters using P 4 S 10 , a thiol (RSH), and a multicarboxylic acid precursor, and (ii) the subsequent utilization of these dithioesters to prepare ABA-type triblock copolymers and three-arm polystyrene stars by RAFT.…”
Section: Introductionmentioning
confidence: 99%
“…The RAFT agent, cyanoisopropyl dithiobenzoate was synthesized and purified according to Duréault et al [30], by the reaction of phosphorus pentasulfide (Aldrich), AIBN, and benzoic acid (Fluka) in toluene (Merck). All the reactants for the synthesis of CPDB were used as received.…”
Section: Methodsmentioning
confidence: 99%